Description of Historical Awareness of Class XII Social Sciences Students in High School - Putriyatul Hikmah (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to find out which indicators of historical awareness are still low for class XII Social Sciences students and the causes of these low indicators of historical awareness. Methodology: This research is included in descriptive research where data is collected to explain solutions to current problems based on data. The research location is at State High School 1 Pariangan, Pariangan District, Tanah Datar Regency. The objects of this research were 60 students of class XII Social Sciences State High School 1 Pariangan. Data collection was carried out through distributing questionnaires. Data analysis techniques use percentage analysis, frequency distribution, data centering using the mean, median and mode formula, and data variation analysis using the standard deviation formula. Main Findings: Based on the analysis obtained, it shows that in general the picture of historical awareness of class XII Social Sciences students is in the very high category, namely 88.33%. However, not all class XII Social Sciences students meet the very high category. If you look at the percentage of each indicator, students' historical awareness is already high. If you look at the seventeen items, thirteen items are high, there are four items that are not high enough, namely past experience items that are believed to be able to solve the problems faced. Novelty/Originality of this study: This research provides insight into students' historical awareness, shows contributions to the understanding of specific issues at the high school level, and offers directions for further improvements in history learning. Although students' general level of historical awareness is high, there are still areas that need further attention and improvement. This can be a basis for designing interventions or educational programs that focus more on indicators that are still low.